Clinical Dental Care Epidemiology, Prevalence, Symptoms and Routes of Transmission of Coronavirus Disease 19: A Systematic Review of Literature and Meta-Analysis - Ali Amiri; Pantea Moradinejad; Sara Jafarizadeh; Zahra Sadat Tabatabaei Jebeli (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the epidemiological evidence, symptoms, and transmission routes of Coronavirus Disease 19 for clinical dental care. Material and Methods: PubMed, Embase, ISI, Scopus, Medicine have been used to search for articles until October 2020. Therefore, EndNote X9 was used to manage electronic resources. A 95% confidence interval (CI) effect size, random effect model, and the REML method were evaluated. Forty-one articles were found. In the first step of selecting studies, 40 studies were selected to review the abstracts. Finally, six studies were selected. Results: The effect size of symptoms of COVID-19 was fever: 92% (ES = 0.92, 95% CI 0.79-1.06), cough: 73% (ES = 0.73, 95% CI 0.59-0.88), headache: 8% (ES = 0.8, 95% CI 0.06-0.22), myalgia 13% (ES = 0.13, 95% CI 0.01-0.27) and nasal congestion 22% (ES = 0.22, 95% CI 0.06-0.39). The following recommendations are appropriate during COVID-19 for dental emergency management: personal protective equipment and hand cleanliness practices, personal protective equipment (PPE), preprocedural mouth rinse, single-use (disposable), cone-beam computed tomography (CBCT) and periapical (PA) radiography, Rubber dam, sodium hypochlorite for root canal irrigation, disinfect inanimate surfaces, ultrasonic scaling instruments and airborne infection isolation. Conclusion: Fever should be used as the first sign in the diagnosis; dentists should measure the fever of all patients at the time of arrival and before any procedure and then ask about other symptoms.